Comparative adsorption of copper (II) and lead (II) from aqueous solutions on soursop (annona muricata) leaves / Nur Sabarina Syahirah Mohd Fathi - Mohd Fathi, Nur Sabarina Syahirah (Faculty Of Applied Sciences, 2019)
The investigation regarding the potential of soursop (Annona muricata) leaves as an adsorbent for the comparatives removal of Cu2+ and Pb2+ ions from aqueous solutions was conducted. The influence of pH, dosage, contact time and initial metal concentrations were studies in batch experiments at room temperature (298 K). The AML used in this study was characterized by FTIR spectroscopy. The presence of OH, -NH2, C=S, -CO, and C=O groups was presented during analysis of FTIR spectra. One of the main mechanisms for the removal of Cu2+ and Pb2+ was complexation as indicated by FTIR spectra. The pHzpc value of the AML was 5.98 and the maximum metal adsorption was at pH 5. The result at effect of dosage also indicated that the percentage removal of heavy metal ions (Cu2+ and Pb2+) was increasing with the increasing of amount of dosage. From the result, it is showed that the maximum percentage removal for Pb2+ ( 97.98%) is higher compared to Cu2+ (82%). The adsorption for both heavy metal ions was rapid at the first 5 minutes of contact, however slowly achieved the equilibrium time at 45 minutes agitation. Kinetic studies showed good correlation coefficient for the Pseudo-second order kinetic model. Meanwhile, Langmuir model was indicated to be more fitted than Freundlich model for the equilibrium data which gives R2 = 0.9987 for Cu2+ ion and R2 = 0.9515 for Pb2+ ion. Based on the FTIR spectra, kinetic and isotherm studies, it can be concluded that the higher adsorption of heavy metal ions onto the AML is Cu2+ ion.